(Bi0.5Na0.5)TiO3:Tb3+: A New Green Emission Multifunctional Ferroelectric Material. Issue 1 (2nd January 2016) - Hai-Qin, Sun; Qi-Wei, Zhang; Wen-Xin, Li
Abstract : The photoluminescence of Tb 3+ -doped (Bi0.5 Na0.5 )TiO3 (BNT) ferroelectric materials fabricated via the conventional solid-sate reaction method were studied. Under blue light excitation (487 nm), a bright green emission centered at 547 nm is observed at room temperature, originating from the 5 D4 → 7 F5 transition of Tb 3+ ions. The emission intensity reached its maximum as the doping concentration is 0.02 mol and sintering temperature is 1080°C, respectively. The CIE chromaticity coordinate for x = 0.02 is (0.3222, 0.6711), located in the green light region. These results show that Tb 3+ -doped BNT materials may have potential applications in white light-emitting diodes and novel multifunctional devices.